Proceedings of the 5th International Conference on Multimodal Interfaces 2003
DOI: 10.1145/958432.958464
|View full text |Cite
|
Sign up to set email alerts
|

Eyetracking in cognitive state detection for HCI

Abstract: 1. Past research in a number of fields confirms the existence of a link between cognition and eye movement control, beyond simply a pointing relationship. This being the case, it should be possible to use eye movement recording as a basis for detecting users' cognitive states in real time. Several examples of such cognitive state detectors have been reported in the literature. 2.A multi-disciplinary project is described in which the goal is to provide the computer with as much real-time information about the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Previous research has shown that users' pupils dilate when the difficulty of the task and their cognitive effort to solve it increase [6,19,20,18,14]. Many studies have validated this argument across a variety of tasks, including reading, problem solving, and visual tasks [21]. Porta et al [19] also observed a decrease in pupil diameter size towards the end of the task in their experiment, interpreting it as a potential sign for tiredness.…”
Section: Pupil Dilationmentioning
confidence: 83%
See 3 more Smart Citations
“…Previous research has shown that users' pupils dilate when the difficulty of the task and their cognitive effort to solve it increase [6,19,20,18,14]. Many studies have validated this argument across a variety of tasks, including reading, problem solving, and visual tasks [21]. Porta et al [19] also observed a decrease in pupil diameter size towards the end of the task in their experiment, interpreting it as a potential sign for tiredness.…”
Section: Pupil Dilationmentioning
confidence: 83%
“…Thus, the state of attention is indicated by the position of the gaze within the display or a specific AOI. Rudmann et al [21] found that the gaze direction indicates the interface element that is relevant for the current cognitive activity. It can be interpreted as a repeated interest in an area.…”
Section: Fixationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The human eye reads a line of text in discrete chunks through a series of fixations and fast eye movements to take in the next section [13]. Eye tracking is based on the fact that a record of a person's eye movements while doing a task provides information about the nature, sequence and timing of the cognitive operations that took place [14].…”
Section: Related Usability Studiesmentioning
confidence: 99%